2021
DOI: 10.3390/s21041229
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Matrix Optimization for Compressed Sensing System with Constructed Dictionary via Takenaka–Malmquist Functions

Abstract: Compressed sensing (CS) has been proposed to improve the efficiency of signal processing by simultaneously sampling and compressing the signal of interest under the assumption that the signal is sparse in a certain domain. This paper aims to improve the CS system performance by constructing a novel sparsifying dictionary and optimizing the measurement matrix. Owing to the adaptability and robustness of the Takenaka–Malmquist (TM) functions in system identification, the use of it as the basis function of a spar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…먼저 많은 계산량과 메모리를 필 요로 한다 [4] . 두 번째로 센싱 행렬식의 필수 요구 조건인 ristricted isometry property(RIP) 조건을 검증하는 효율적인 알고리즘이 없어서 성능을 확신하기 어렵다 [5] . 결정 센싱 행렬식(deterministic sensing matrix)은 메모리 문제를 해결 하며 빠르게 구현할 수 있는 구조로, 앞의 랜덤 센싱 행렬 식의 단점을 보완할 수 있다 [6] .…”
Section: ⅰ 서 론unclassified
“…먼저 많은 계산량과 메모리를 필 요로 한다 [4] . 두 번째로 센싱 행렬식의 필수 요구 조건인 ristricted isometry property(RIP) 조건을 검증하는 효율적인 알고리즘이 없어서 성능을 확신하기 어렵다 [5] . 결정 센싱 행렬식(deterministic sensing matrix)은 메모리 문제를 해결 하며 빠르게 구현할 수 있는 구조로, 앞의 랜덤 센싱 행렬 식의 단점을 보완할 수 있다 [6] .…”
Section: ⅰ 서 론unclassified
“…In recent years, many researchers have put forward many principles and methods to construct [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and optimize [34][35][36] measurement matrices. This paper mainly studies the construction method of deterministic measurement matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Elad [51] launched an algorithmic design for a sensing matrix by minimizing the average measure of the coherence iteratively. In [52][55], several algorithms have been proposed for optimizing a sensing matrix, where each one attempts to approximate its Gram matrix to that of an equiangular tight frame (ETF) [56]. In [57], Chen et al demonstrated that a unit-norm tight frame is a closest design of a nearly orthogonal matrix.…”
Section: Introductionmentioning
confidence: 99%